Total synthesis of the marine natural product solomonamide B necessitates stereochemical revision - Kashinath, K.; Jachak, Gorakhnath R.; Athawale, Paresh R.; Marelli, Udaya Kiran; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Organic Letters, 2016)
The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the H-1 and C-13 NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal olefins in a macrocyclic setting.

Total synthesis of the potent anti-inflammatory natural product solomonamide A along with structural revision and biological activity evaluation - Jachak, Gorakhnath R.; Athawale, Paresh R.; Agarwal, Heena; Barthwal, Manoj Kumar; Lauro, Gianluigi; Bifulco, Giuseppe; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2018)
Herein, we report the total synthesis of solomonamide A along with its structural revision for the first time. The natural product possesses very potent anti-inflammatory activity, and it contains a macrocyclic peptide having four consecutive stereocenters on an unnatural amino acid component. The key features in the present synthesis include the application of an Evans aldol reaction, ligand-free Heck macrocyclization and chemoselective oxidations. The challenging task of fixing the stereochemistry of OH at the C5-position was accomplished with the help of DFT calculations, applying a quantum-mechanical (QM)/NMR combined approach. Biological evaluation in a mouse paw edema model revealed that a low dose (0.3 mg kg(-1)) of the synthesized solomonamide A showed 74% reduction at 6 h, which was comparable to a high dose (10 mg kg(-1)) standard drug dexamethasone effect (75% at 6 h). Thus, we further confirmed the revised structure of solomonamide A.

Tuning of alpha-silyl carbocation reactivity into enone transposition: application to the synthesis of peribysin D, E-volkendousin, and E-guggulsterone - Athawale, Paresh R.; Zade, Vishal M.; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Organic Letters, 2021)
A reliable method for enone transposition has been developed with the help of silyl group masking. Enantio-switching, substituent shuffling, and Z-selectivity are the highlights of the method. The developed method was applied for the first total synthesis of peribysin D along with its structural revision. Formal synthesis of E-guggulsterone and E-volkendousin was also claimed using a short sequence.